Developing a Formative Assessment Based on Self-directed Learning Oriented Assessment (SLOA) for Circle Topics in Senior High School - Khiara Ching Prasetya; Chairil Faif Pasani; Taufiq Hidayanto; Zainudin bin Hassan (Universitas Lambung Mangkurat, 2026)
The implementation of the Merdeka Curriculum emphasizes meaningful learning processes supported by appropriate assessment practices. In mathematics learning, formative assessment is essential for monitoring students’ conceptual understanding and learning progress. However, existing practices remain predominantly teacher-centered and provide limited opportunities for students to engage in reflection and self-assessment, and studies integrating student-centered assessment approaches in senior high school mathematics are still limited. This study aims to develop a formative assessment based on Self-directed Learning Oriented Assessment (SLOA) for circle topics in senior high school that is valid, practical, and effective. SLOA is an assessment approach that promotes self-directed learning by integrating reflection, monitoring, and self-evaluation into the assessment process. This study employed a research and development approach using the ADDIE model. The study involved 26 grade XI students in one class at SMAN 7 Banjarmasin without a control group. The instruments included expert validation sheets, essay-type formative tests, self-assessment questionnaires, and a teacher practicality questionnaire. The results showed that the formative tests and self-assessment questionnaires were highly valid, with average scores of 3.50 and 3.46 on a 4-point scale. The practicality score reached 80%, categorized as very practical. Based on a minimum passing grade of 75 and a classical completeness criterion of 85%, the implementation results showed that 92% of students in the first test and 96% in the second test achieved mastery. These findings indicate that SLOA-based formative assessment is feasible and effective in supporting students’ self-directed learning and provides practical implications for mathematics teachers in implementing more student-centered assessment practices.